On the importance of the sowing time of crucifers in preventing the damage caused by cabbage maggots (Hylemyia spp), on the basis of tests made on big-leafed turnip - Varis, Anna-Liisa (Agricultural and Food Science, 1958)
In investigating the importance of the sowing time of crucifers in preventing the damage caused by the cabbage maggots (Hylemyia spp) the big-leafed turnip (Brassica rapa L. v. rapifera Metzg.) was used as a test plant. In regard to the abundance and severity of the damage differences occured in the test plants sown at different times. In South-Finland, however, the order varied in different years so that damage caused by the cabbage maggots can generally not be avoided by an arrangement of the sowing time. In North-Finland the early sowings were generally somewhat more severely damaged than the later ones. The postponement of the sowing time, however, had a detrimental effect on the yields and despite the fairly severe damage the best yields were obtained from the early sowings. Kylvöajan merkitystä on selvitetty Tikkurilassa ja Rovaniemellä järjestettyjen kylvö- ja korjuuaikakokeiden yhteydessä. Sopivana koekasvina on pidetty naattinaurista, koska se kehittyy nopeasti, ja se voidaan täten kylvää myös melko myöhään. Eri kylvöaikojen välillä on kaalikärpäsvioitukseen nähden ollut jonkin verran eroja. Etelä-Suomessa vioituksen runsauden ja voimakkuuden mukainen järjestys on kuitenkin vaihdellut eri vuosina, joten kylvöajan järjestelyllä ei yleensä voida välttää kaalikärpäsvioitusta. Pohjois-Suomessa on aikaisissa kylvöksissä yleensä ollut jonkin verran enemmän vioitusta kuin myöhäisissä. Kylvöajan siirtyessä myöhäisemmäksi sadot ovat kuitenkin laskeneet tuntuvasti, ja kohtalaisen runsaasta vioituksesta huolimatta parhaat sadot on saatu aikaisista, Rovaniemen seudulla toukokuun lopulla ja kesäkuun alussa suoritetuista kylvöistä. Kylvöajan valinnalla ei siis kaalikärpäsvioituksen kannalta näytä olevan käytännöllistä merkitystä niinkään nopeasti kasvavalla kasvilla kuin naattinauriilla.